Pengaruh Beban Kerja Terhadap Kinerja Petugas Inspektur Keamanan Penerbangan Di Kantor Otoritas Bandar Udara Wilayah III Surabaya - Elnia Frisnawati; Ayya Rahmadinata (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
To support a good flight There are several aspects that must be considered so that the flight can take place safely and comfortably. One of wich is terms of security aspect. In this endemic era, employees have problems in carrying out their duties due to the inaccessibility of some work areas because of the limited budget issued by the central government. With the inaccessibility of some work areas will be able to affect the results of the employee’s own performance in completing the predetermined target. Therefore, the researcher wants to examine the workload of flight security inspectors at the Surabaya Regional III Airport Authority Office. Keywords: Workload, Performance